Heterozygous FGA p.Asp473Ter (fibrinogen Nieuwegein) presenting as antepartum cerebral thrombosis. Issue 163 (March 2018) - Tajdar, Mercedeh; Orlando, Christelle; Casini, Alessandro; Herpol, Margaux; De Bisschop, Barbara; Govaert, Paul; Neerman-Arbez, Marguerite; Jochmans, Kristin
Abstract: Introduction: The propositus – a two-week-old boy – was transferred to our university hospital for investigation of increased head circumference and full fontanel. On ultrasound, thrombosis of the right internal cerebral vein and intraventricular haemorrhage was diagnosed, confirmed by MRI. Family history revealed a bleeding history in the mother. A haemostatic work-up in both mother and child was performed in order to rule out congenital coagulopathy. Aim: We document a clinical case of congenital dysfibrinogenemia, caused by heterozygosity for the mutation FGA p.Asp473Ter, previously reported as fibrinogen Nieuwegein in homozygosity in an asymptomatic patient. Methods: Fibrinogen activity in plasma was determined by functional Clauss assay, and immunological fibrinogen concentration by nephelometry. In vitro fibrin clot investigations and genetic analysis of the fibrinogen gene were performed. Complete haemostatic work-up was done by conventional methods. Results and discussion: After full laboratory work-up, dysfibrinogenemia was diagnosed, based on fibrinogen activity:antigen ratio, thrombin time, and reptilase time. Molecular analysis showed a frameshift mutation in exon 5 of FGA : c.1415_1416 insC, leading to a termination codon immediately after the insertion (CCT GAT > CCC TGA) and resulting in a truncated αC-domain. This mutation has been reported earlier as fibrinogen Nieuwegein. Further in vitro investigations revealed an abnormally tight clot structure, prolonged clot lysis time and affected polymerization, suggesting a thrombotic phenotype. Cerebral imaging revealed thrombosis, most likely developed in the antenatal period, leading to extensive intraventricular haemorrhage and posthaemorrhagic ventricular dilatation. Conclusion: We highlight the combined thrombotic and haemorrhagic phenotype linked to heterozygous fibrinogen Nieuwegein, in contrast to the previously reported asymptomatic homozygous case. Highlights: A prenatal internal cerebral vein thrombosis causes intraventricular haemorrhage. Congenital dysfibrinogenemia with a heterozygous mutation FGA p.Asp473Ter is reported. Our case contrasts with asymptomatic reports of this mutation in homozygosity.